2011
DOI: 10.1039/c1cc11985k
|View full text |Cite
|
Sign up to set email alerts
|

Reversible pressure-induced amorphization of a zeolitic imidazolate framework (ZIF-4)

Abstract: We report the reversible pressure-induced amorphization of a zeolitic imidazolate framework (ZIF-4, [Zn(Im)(2)]). This occurs irrespective of pore occupancy and takes place via a novel high pressure phase (ZIF-4-I) when solvent molecules are present in the pores. A significant reduction in bulk modulus upon framework evacuation is also observed for both ZIF-4 and ZIF-4-I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
197
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 209 publications
(217 citation statements)
references
References 15 publications
20
197
0
Order By: Relevance
“…In the past, a lot of work has focused on the mechanical properties (elastic moduli, hardness) of MOFs and ZIFs, both experimentally [38][39][40] and computationally. 41,42 The occurrence of pressure-induced crystal-to-crystal and crystal-to-amorphous transitions has been solidly established in several frameworks, including ZIF-8, 43 ZIF-4, 44 and the nonporous ZIF-zni. 45 Here, we try to shed light into the generality of this pressure-induced transitions by our systematic approach, modelling the behavior under pressure of 10 different ZIFs with identical chemical composition (Zn(im) 2 ), at the same level of molecular modelling.…”
Section: -mentioning
confidence: 99%
“…In the past, a lot of work has focused on the mechanical properties (elastic moduli, hardness) of MOFs and ZIFs, both experimentally [38][39][40] and computationally. 41,42 The occurrence of pressure-induced crystal-to-crystal and crystal-to-amorphous transitions has been solidly established in several frameworks, including ZIF-8, 43 ZIF-4, 44 and the nonporous ZIF-zni. 45 Here, we try to shed light into the generality of this pressure-induced transitions by our systematic approach, modelling the behavior under pressure of 10 different ZIFs with identical chemical composition (Zn(im) 2 ), at the same level of molecular modelling.…”
Section: -mentioning
confidence: 99%
“…Recent studies have revealed that ZIFs may undergo thermally-and/or pressure-induced amorphisation that reinforces the similarity between ZIFs and silica. [3][4][5] However, important differences between ZIFs and silica systems are still ignored in the literature. For example, it is well known that the thermodynamic 'ground state' of the silica system at ambient conditions corresponds to the a-quartz phase (qtz net) 6 , whereas the quartz-like topology is hardly accessible in the Zn(im) 2 (im = imidazolate) system as was shown in our previous ab initio study.…”
mentioning
confidence: 99%
“…For comparison, we have also investigated the thermal effects on the vibrational spectra of ZIF-8 (whose linker is mIm = 2-methylimidazolate), which does not amorphize thermally. 21 It is worth noting that these materials can also amorphize through other sources of external stimuli, such as pressure 22 and mechanical impact. 23 However, it has been suggested that the mechanisms for the various routes to amorphization are different, with a shear instability being the likely cause of the mechanically induced amorphization.…”
mentioning
confidence: 99%